Joseph Arch (1826-1919)
1880 1850-1880 "Joseph Arch (1826-1919)" [T0209.jpg], 1850-1880 Joseph Arch (1826-1919) was a farm labourer and Primitive Methodist lay preacher from Barford, Warwickshire. Following his speech to a mass meeting of 2000 labourers at Wellesbourne in February 1872, the Warwickshire Agricultural Labourers' Union was formed with Arch as secretary. Later that year he established a National Agricultural Labourers' Union which had enrolled 100,000 members by the end of 1873. The union received widespread support from the Labour movement and there were some spectacular but short lived wage advances, e.g. labourers' wages in Warwickshire were increased 25% to 16 shillings (80p) per week. Then farm produce price slumped and labourers faced ruthless lockouts and evictions from their tied cottages. The influence of Arch's union was gradually broken, disappearing in the 1890s. Arch was elected to the North West Norfolk constituency in 1885.